The permeation barrier of plant cuticles: uptake of active ingredients is limited by very long‐chain aliphatic rather than cyclic wax compounds. Issue 12 (3rd October 2019) - Staiger, Simona; Seufert, Pascal; Arand, Katja; Burghardt, Markus; Popp, Christian; Riederer, Markus
Abstract: BACKGROUND: The barrier to diffusion of organic solutes across the plant cuticle is composed of waxes consisting of very long‐chain aliphatic (VLCA) and, to varying degrees, cyclic compounds like pentacyclic triterpenoids. The roles of both fractions in controlling cuticular penetration by organic solutes, e.g. the active ingredients (AI) of pesticides, are unknown to date. We studied the permeability of isolated leaf cuticular membranes from Garcinia xanthochymus and Prunus laurocerasus for lipophilic azoxystrobin and theobromine as model compounds for hydrophilic AIs. RESULTS: The wax of P. laurocerasus consists of VLCA (12%) and cyclic compounds (88%), whereas VLCAs make up 97% of the wax of G. xanthochymus . We show that treating isolated cuticles with methanol almost quantitatively releases the cyclic fraction while leaving the VLCA fraction essentially intact. All VLCAs were subsequently removed using chloroform. In both species, the permeance of the two model compounds did not change significantly after methanol treatment, whereas chloroform extraction had a large effect on organic solute permeability. CONCLUSION: The VLCA wax fraction makes up the permeability barrier for organic solutes, whereas cyclic compounds even in high amounts have a negligible role. This is of significance when optimizing the foliar uptake of pesticides. © 2019 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Cuticular uptake of active ingredients is of major importance for foliar‐applied agrochemicals. We studied the importance of very long‐chain aliphatic and cyclic wax fractions for cuticular permeability.